Chicken chicken - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1997)
Everyone in Goshen Falls knows about weird Vanessa. She dresses all in black and wears black lipstick. People say she puts spells on people. Crystal and her brother Cole made Vanessa mad. After she whispered that strange warning, "Chicken chicken" something weird has happened. Crystal's lips have turned as hard as a bird's beak, and Cole has started growing ugly white feathers all over his body.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
Keywords: Horror tales; Chickens -- Juvenile fiction; Children's stories; Horror fiction